Therapeutic itinerary of the family and adolescent with type i mellitus diabetes El itinerario terapéutico del adolescente con diabetes mellitus tipo i y sus familiares Itinerário terapêutico do adolescente com diabetes mellitus tipo 1 e seus familiares - Mariza Maria Serafim Mattosinho; Denise Maria Guerreiro Vieira da Silva (Universidade de São Paulo, 2007)
This is a qualitative assistential convergent study. Its main objective is to understand the therapeutic itinerary of adolescents with type 1 mellitus diabetes, as well as that of their families. The sample was composed of adolescents, between 15 and 25 years old, involved with a health institution in Florianópolis through the Health Care model that includes professional, family, and popular subsystems. Data were obtained through in-depth interviews and field observation of 20 people (relatives and adolescents with diabetes). The data analysis included data codification and categorization. Two categories were constructed: Decisions and negotiations about health, care and treatment; and the journey through the three subsystems of health care. The study permitted to understand that the treatment and care within the professional subsystem are not the only ones available. There are different practices in health performed from the evaluation each family makes, of what they believe adequate for their adolescent with diabetes. Estudio de naturaleza cualitativa, de tipo convergente-asistencial, tuvo como objetivo comprender el camino terapéutico de los adolescentes con diabetes mellitus tipo I y sus familiares, vinculados a una institución de salud de Florianópolis, entre las edades de 15 y 25 años, a través del modelo del Cuidado para la Salud, que incluye los subsistemas profesional, familiar y popular. Los datos fueron obtenidos a través de la entrevista en profundidad y la observación de campo con 20 personas (familiares y adolescentes con diabetes). El análisis incluye la codificación y la categorización de los datos. Fueron construidos dos categorias: Las decisiones y negociaciones sobre la salud, los cuidados y los tratamientos y El percurso en los tres subsistemas de la salud. El estudio permitió comprender que los tratamientos y los cuidados del subsistema profesional no son los únicos, existiendo diferentes prácticas en la salud que son realizadas a partir de la evaluación que cada familia hace a partir de aquello que considera adecuado para el adolescente con diabetes mellitus. Estudo de natureza qualitativa, do tipo convergente assistencial, objetivou compreender o itinerário terapêutico de adolescentes com diabetes mellitus tipo 1 e seus familiares, vinculados a uma instituição de saúde de Florianópolis, SC. Foi utilizado o modelo de Cuidado à Saúde de Kleinman que inclui os subsistemas profissional, familiar e popular. Os dados foram obtidos através de entrevistas semi-estruturadas e observação de campo com vinte pessoas: familiares e adolescentes com diabetes. A análise incluiu a codificação e categorização dos dados. Foram construídas duas categorias: decisões e negociações sobre a saúde, os cuidados e os tratamentos e o percurso nos três subsistemas de saúde. O estudo permitiu compreender que os tratamentos e cuidados do subsistema profissional não são únicos, havendo diferentes práticas em saúde que são realizadas a partir da avaliação que cada família faz daquilo considera adequado para o adolescente com diabetes mellitus.